THE STANDARD-LEGAL ASPECTS OF ORGANIZATIONAL ADMINISTRATIVE ACTIONS FOR PREVENTIVE MAINTENANCE OF THE INFLUENZA AND ARVI - Golovanova, I.A.; Gapon, O.V.; Filatova, V.L. (World of Medicine and Biology, 2012)
The system analysis of standard-legal acts in sphere of preventive maintenance of the influenza, acute respiratory virus infection is carried out. Performance state is standard-legal certificates at local level is provided by means of functionally structural model of organizational administrative actions where as their organizer bodies of local authorities and the state self-management act. Executors of 1st level are medical educational institutions, mass media, sanitary epidemiological services, 2nd level – medical aid station which directly carry out preventive maintenance.
Keywords: normatively-legal aspects; organizationally-administrative measures; prophylaxis; flu; ARVI